Can redistribution contribute to pollution reductions? An empirical evaluation - Thomas Drosdowski (Luxembourg Income Study (LIS), 2006)
We test the hypothesis that more progressive redistribution contributes to emission reductions with the aid of fixed-effects estimation technique. Using a panel of 16 West European countries over the period 1990-00, we regress emission levels of four different air pollutants on two alternative measures of redistribution and additional controls. The results are statistically significant and indicate that redistribution may be an important driving force of environmental improvements.
Keywords: 330; Umweltbelastung; Gerechtigkeit; Verteilungspolitik; Schätzung; Westeuropa